Differential Prescribing of Opioid Analgesics According to Physician Specialty for Medicaid Patients with Chronic Noncancer Pain Diagnoses - Chris Ringwalt; Hallam Gugelmann; Mariana Garrettson; Nabarun Dasgupta; Arlene E Chung; Scott K Proescholdbell; Asheley Cockrell Skinner (Pain Research and Management)
BACKGROUND: Despite >20 years of studies investigating the characteristics of patients seeking or receiving opioid analgesics, research characterizing factors associated with physicians’ opioid prescribing practices has been inconclusive, and the role of practitioner specialty in opioid prescribing practices remains largely unknown.